Uji Efektifitasi Alat Sterilisator Ultra Violet C BC19 di Laboraturium Entomologi Fakultas Kesehatan Msyarakat Universitas Diponegoro - Rayendra, Muhammad Fikri; Laksono, Budi; Martini, Martini (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Air is the most important component in life, and according to data, viruses always mutate rapidly, causing an increase in airborne diseases (Airbone Disease). There is a need for a tool to address this issue, leading to the creation of the BC19 device, an invention developed by Budi Laksono to decontaminate airborne bacteria. The BC19 device is an Ultraviolet-C sterilization tool with the smallest wavelength. The purpose of this study is to identify the genus of bacteria present in the room and to determine the use of this device in a closed room (Entomology Laboratory Room, FKM UNDIP).Methods: The research method used was a pre-post experimental design, in which there were interventions before and after treatment with BC19 sterilization for 22 minutes and 66 minutes, with air bacteria sampling using Plate Count Agar (PCA) in three locations representing the Entomology Laboratory of the Faculty of Public Health, Diponegoro University.Result: Based on the findings of this study, it was found that there were two genera of bacteria, namely Bacillus sp and Strephylococcus sp, which are classified as Gram-positive. It was also found that there was a difference in the average number of bacterial colonies on Petri dishes between the groups before and after BC19 treatment.Conclusion: Gram staining revealed Bacillus sp and Strephylococcus sp bacteria with Gram-positive results, and the device was proven to be able to decontaminate airborne bacteria.